Development of a Web-Based Digital Rental Platform for Party and Event Equipment Using a User-Centered Design Approach - Syahputra, Zulfahmi (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
Digitalization has become increasingly essential for service-based micro and small enterprises, including businesses that provide party and event equipment rentals. Traditional rental workflows such as manual communication, inconsistent stock updates, and the absence of transparent availability information often hinder operational efficiency and customer satisfaction. To address these challenges, this study aims to develop a web-based digital rental platform for party and event equipment using a User-Centered Design (UCD) approach. UCD was selected because it emphasizes continuous user involvement throughout the system development lifecycle, ensuring that the resulting platform aligns with real user needs and usability expectations. The research was conducted through four key stages: user requirement analysis, iterative prototyping, system implementation, and usability evaluation. Data were collected through interviews, observation, and user testing involving both customers and rental administrators. The final system provides a structured equipment catalog, real-time availability display, an intuitive booking workflow, and an administrative dashboard for managing inventory and rental schedules. Usability evaluation using the System Usability Scale (SUS) yielded a score of 82.4, indicating excellent usability. Task completion rates improved significantly, and user feedback highlighted enhanced clarity, reduced interaction errors, and faster rental processing. The findings demonstrate that adopting UCD contributes to the development of a more intuitive, efficient, and user-validated rental platform. This study provides practical insights into the application of UCD in service-oriented digital systems and supports ongoing efforts to modernize rental operations through web-based solutions